A Critical Evaluation of Pedophilia from a Biopsychosocial Perspective - Wimaladhamma Thero, Koonkandawala (Faculty of Graduate Studies, University of Kelaniya, 2015)
Child abuse is one of the most important and crucial topics not only in present Sri Lanka but also in whole world. Among the many forms of child abuse, sexual abuse holds a higher place. Sometimes, the victims of sexual abuses are killed. However, in Sri Lanka, number of sexual abuses of little children; both males and females has increased. Over 1500 cases related to children reported per year in Sri Lanka. In modern Psychology, sexual attraction to little children and interest to engage in sexual activities with little children (generally aged 13 or younger) is considered as an abnormal behavior. This abnormal or psychopathological behavior is a mental disorder which is named as ''pedophilia" or ''pedophilic disorder" in Diagnostic and Statistical Manual of Mental Disorders-V (DSM-V). The American Psychiatric Association (APA) has included ''pedophilia" as a mental disorder in its DSM since 1968. There are various types of pedophilias and various perspectives and approaches try to understand ''pedophilia" from their view points. Here, an attempt is made to understand and explain "pedophilia" from a biopsychosocial perspective. Here, with the newest findings of research studies about ''pedophilia," from biological, neurobiological environmental and psychological perspectives, the sufficient and necessary causes and facts about ''pedophilic disorder" will be discussed.
Keywords: Pedophilia; DSM-V; Neurobiology; Environment; Psychology; Mental Disorder